A Case of Self‐Organization in Highly Emissive EuIII Ionic Liquids. Issue 28 (1st August 2017) - Leal, João P.; Outis, Mani; Casimiro, Maria H.; Ferreira, Luis M.; Fernandes, Fábio; Monteiro, Bernardo; Laia, César A. T.; Pereira, Cláudia C. L.
Abstract : Intrinsic photoluminescent ionic liquids based on europium(III) tetrakis(β‐diketonate) complexes with a tetraalkylphosphonium as the counterion were synthesized. Two are room temperature ionic liquids; [P6, 6, 6, 14 ][Eu(fod)4 ] (1 ) {fod is 1, 1, 1, 2, 2, 3, 3‐heptafluoro‐7, 7‐dimethyloctane‐4, 6‐dionate} and [P6, 6, 6, 14 ][Eu(fod)3 (dbm)] (2 ) {dbm is dibenzoylmethanate}, while calorimetric measurements showed a melting point at 415 K for [P6, 6, 6, 14 ][Eu(dbm)4 ] (3 ). The luminescence quantum yields determined for1, 2, and3 are 34, 59 %, and 64 %, respectively. The photoluminescence and thermochemical properties of the complexes were investigated in detail and the influence of the long chain tetraalkylphosphonium counterion, together with the aromatic diketone ligand, on the unusual thermal behavior of2 is discussed. Abstract : The intrinsic photoluminescence of three ionic liquids based on europium(III) tetrakis(β‐diketonate) complexes with a tetraalkylphosphonium as a counter ion is reported. A complex presented an unusual thermal behavior attributed to the presence of a cation with a long alkyl chain. The thermochemistry is thoroughly discussed.